THE EFFECT OF LIFESTYLE AND STORE ATMOSPHERE ON CONSUMER PURCHASE DECISIONS THROUGH PURCHASE INTEREST OF INDOMARET IN TERNATE - Ayu Qur'naesih Rusdiyanto; Ida Hidayanti; Ririn Damayanti (Journal of Management and Islamic Finance, 2022)
This study aims to determine the effect of lifestyle and store atmosphere on consumer purchasing decisions through purchase interest. This research was a quantitative research. The population in this study was Indomaret consumers in Ternate City with a non-probability sampling method and a purposive sampling approach. The data analysis technique in this research used path modeling analysis using smart Partial Least Square (PLS) version 3 as a statistical test tool. The results of this study indicate that lifestyle has a significant effect on purchase decisions, store atmosphere has a significant effect on purchase decisions, lifestyle has a significant effect on puerchase interest, store atmosphere has a significant effect on purchase interest.